Don't Fear the Reefer—Evidence Mounts for Plant-Based Cannabidiol as Treatment for Epilepsy. Issue 2 (March 2019) - Perry, M. Scott
: Effect of Cannabidiol on Drop Seizures in the Lennox-Gastaut Syndrome Devinsky O, Patel AD, Cross JH, et al; GWPCARE3 Study Group. N Engl J Med . 2018;378:1888-1897. doi:10.1056/NEJMoa1714631 Background: Cannabidiol has been used for treatment-resistant seizures in patients with severe early-onset epilepsy. We investigated the efficacy and safety of cannabidiol added to a regimen of conventional antiepileptic medication to treat drop seizures in patients with the Lennox-Gastaut syndrome, a severe developmental epileptic encephalopathy. Methods: In this double-blind, placebo-controlled trial conducted at 30 clinical centers, we randomly assigned patients with the Lennox-Gastaut syndrome (age range, 2-55 years) who had had 2 or more drop seizures per week during a 28-day baseline period to receive cannabidiol oral solution at a dose of 20 mg/kg of body weight (20-mg cannabidiol group) or 10 mg/kg (10-mg cannabidiol group) or matching placebo, administered in 2 equally divided doses daily for 14 weeks. The primary outcome was the percentage change from baseline in the frequency of drop seizures (average per 28 days) during the treatment period. Results: A total of 225 patients were enrolled; 76 patients were assigned to the 20-mg cannabidiol group, 73 to the 10-mg cannabidiol group, and 76 to the placebo group. During the 28-day baseline period, the median number of drop seizures was 85 in all trial groups combined. The median percentage reduction from baseline in drop seizure frequency during the treatment period was 41.9% in the 20-mg cannabidiol group, 37.2% in the 10-mg cannabidiol group, and 17.2% in the placebo group ( P = .005 for the 20-mg cannabidiol group vs placebo group, and P = .002 for the 10-mg cannabidiol group vs placebo group). The most common adverse events among the patients in the cannabidiol groups were somnolence, decreased appetite, and diarrhea; these events occurred more frequently in the higher dose group. Six patients in the 20-mg cannabidiol group and 1 patient in the 10-mg cannabidiol group discontinued the trial medication because of adverse events and were withdrawn from the trial. Fourteen patients who received cannabidiol (9%) had elevated liver aminotransferase concentrations. Conclusions: Among children and adults with the Lennox-Gastaut syndrome, the addition of cannabidiol at a dose of 10 or 20 mg/kg/d to a conventional antiepileptic regimen resulted in greater reductions in the frequency of drop seizures than placebo. Adverse events with cannabidiol included elevated liver aminotransferase concentrations. (Funded by GW Pharmaceuticals; GWPCARE3ClinicalTrials.gov number, NCT02224560.) : Long-Term Safety and Treatment Effects of Cannabidiol in Children and Adults With Treatment-Resistant Epilepsies: Expanded Access Program Results Szaflarski JP, Bebin EM, Comi AM, et al; CBD EAP Study Group. Epilepsia . 2018;59(8):1540-1548. Objective: Since 2014, cannabidiol (CBD) has been administered to patients with treatment-resistant epilepsies (TREs) in an ongoing expanded access program (EAP). We report interim results on the safety and efficacy of CBD in EAP patients treated through December 2016. Methods: Twenty-five US-based EAP sites enrolling patients with TRE taking stable doses of antiepileptic drugs (AEDs) at baseline were included. During the 4-week baseline period, parents/caregivers kept diaries of all countable seizure types. Patients received oral CBD starting at 2 to 10 mg/kg/d, titrated to a maximum dose of 25 to 50 mg/kg/d. Patient visits were every 2 to 4 weeks through 16 weeks and every 2 to 12 weeks thereafter. Efficacy end points included the percentage change from baseline in median monthly convulsive and total seizure frequency and percentage of patients with ≥50%, ≥75%, and 100% reductions in seizures versus baseline. Data were analyzed descriptively for the efficacy analysis set and using the last-observation-carried-forward method to account for missing data. Adverse events (AEs) were documented at each visit. Results: Of 607 patients in the safety data set, 146 (24%) withdrew; the most common reasons were lack of efficacy (89 [15%]) and AEs (32 [5%]). Mean age was 13 years (range, 0.4-62). Median number of concomitant AEDs was 3 (range, 0-10). Median CBD dose was 25 mg/kg/d; median treatment duration was 48 weeks. Add-on CBD reduced median monthly convulsive seizures by 51% and total seizures by 48% at 12 weeks; reductions were similar through 96 weeks. Proportion of patients with ≥50%, ≥75%, and 100% reductions in convulsive seizures were 52%, 31%, and 11%, respectively, at 12 weeks, with similar rates through 96 weeks. Cannabidiol was generally well tolerated; most common AEs were diarrhea (29%) and somnolence (22%). Significance: Results from this ongoing EAP support previous observational and clinical trial data, showing that add-on CBD may be an efficacious long-term treatment option for TRE. : Randomized, Dose-Ranging Safety Trial of Cannabidiol in Dravet Syndrome Devinsky O, Patel AD, Thiele EA, et al; GWPCARE1 Part A Study Group. Neurology . 2018;90(14):e1204-e1211. Objective: To evaluate the safety and preliminary pharmacokinetics of a pharmaceutical formulation of purified cannabidiol (CBD) in children with Dravet syndrome. Methods: Patients aged 4 to 10 years were randomized 4:1 to CBD (5, 10, or 20 mg/kg/d) or placebo taken twice daily. The double-blind trial comprised 4-week baseline, 3-week treatment (including titration), 10-day taper, and 4-week follow-up periods. Completers could continue in an open-label extension. Multiple pharmacokinetic blood samples were taken on the first day of dosing and at end of treatment for measurement of CBD, its metabolites 6-OH-CBD, 7-OH-CBD, and 7-COOH-CBD, and antiepileptic drugs (AEDs; clobazam and metabolite N -desmethylclobazam [N-CLB], valproate, levetiracetam, topiramate, and stiripentol). Safety assessments were clinical laboratory tests, physical examinations, vital signs, electrocardiograms, adverse events (AEs), seizure frequency, and suicidality. Results: Thirty-four patients were randomized (10, 8, and 9 to the 5, 10, and 20 mg/kg/d CBD groups and 7 to placebo); 32 (94%) completed treatment. Exposure to CBD and its metabolites was dose proportional (AUC0-t ). Cannabidiol did not affect concomitant AED levels, apart from an increase in N-CLB (except in patients taking stiripentol). The most common AEs on CBD were pyrexia, somnolence, decreased appetite, sedation, vomiting, ataxia, and abnormal behavior. Six patients taking CBD and valproate developed elevated transaminases; none met criteria for drug-induced liver injury and all recovered. No other clinically relevant safety signals were observed. Conclusions: Exposure to CBD and its metabolites increased proportionally with dose. An interaction with N-CLB was observed, likely related to CBD inhibition of cytochrome P450 subtype 2C19. Cannabidiol resulted in more AEs than placebo but was generally well tolerated. Classification of Evidence: This study provides class I evidence that for children with Dravet syndrome, CBD resulted in more AEs than placebo but was generally well tolerated.